Global, regional, and national burden of young COPD, 1990–2021, with forecasts to 2050: a systematic analysis for the global burden of disease study 2021 - Yi Zhu; Tao Shen; Ruixin Guo; Ke Liu; Xiyu Cao; Xiuli Yang; Chuantao Zhang (BMC Public Health)
Abstract Background Young chronic obstructive pulmonary disease (COPD) refers to people with COPD between the ages of 20 and 50 years. Current epidemiological studies focus on local geography, and there is a lack of global-level analysis. This study provides in-depth analyses of the disease burden of young COPD at global, regional, and national levels. Methods This study used the Global Burden of Disease Study 2021 (GBD). The age-standardised prevalence rate (ASPR), age-standardised incidence rate (ASIR), age-standardised death rate (ASDR), and age-standardised disability-adjusted life years (DALYs) rate were used to describe the disease burden. The estimated annual percentage change (EAPC) during the study period was calculated. Joinpoint regression analysis examined the time trend from 1990 to 2021. Annual percentage change (APC) and average annual percentage change (AAPC) were calculated. Risk factors were reported by region and sex. Results In 2021, the global number of young COPD cases was 30,384,539, and the ASPR, ASIR, ASDR, and age-standardised DALYs rates fell slightly. Oceania reported the highest ASPR, ASDR, and age-standardised DALYs rate. High-income North America has the highest ASIR. In 2021, the prevalence, incidence, death, and DALYs rates exhibited similar trends, increasing with age. From 1990 to 2021, both the prevalence and death rates showed a consistent downward trend across all age groups. Joinpoint regression analysis indicated a slight increase in both the ASPR (APC: 0.13; 95% CI: 0.06 to 0.19) and the ASIR (APC: 0.17; 95% CI: 0.10 to 0.24) during the period from 1990 to 1994. The leading DALYs attributable to risk factors for young COPD are household air pollution from solid fuels (20.4%), ambient particulate matter pollution (17.9%), and smoking (13.5%). Conclusions The global burden of ASPR, ASIR, ASDR, and age-standardised DALYs rates in young COPD has decreased, however, the absolute number of patients has increased. The global burden shows noticeable regional differences, with particularly high burdens observed in Oceania. Improving air quality, promoting smoking cessation, and increasing access to lung function tests, raising awareness of young COPD are key strategies for alleviating the burden of young COPD.